Cover Feature: A Unified Approach to Phytosiderophore Natural Products (Chem. Eur. J. 2/2021). Issue 2 (3rd November 2020) - Kratena, Nicolas; Gökler, Tobias; Maltrovsky, Lara; Oburger, Eva; Stanetty, Christian
Abstract : A unified approach towards phytosiderophores is presented in this work, paving the way for ongoing biological investigations (Phytotrace project) of these molecular micronutrient collectors utilized by important food plants like rice, barley, or maize. Two families of these natural products were accessed by stereoselective methods following a divergent, modular synthetic strategy. The syntheses of eight phytosiderophores could be accomplished very efficiently starting from seven appropriate building blocks. Cover image designed and illustrated by Thomas Blaukovitsch. More information can be found in the Communication by C. Stanetty et al. on page 577 .